Free Cinema - Anderson, Lindsay; Reisz, Karel; Richardson, Tony; Mazzetti, Lorenza; Horne, Denis; Goretta, Claude; Tanner, Alain; MacIsaac, Nigel; Vas, Robert; Grigsby, Michael; Russell, Elizabeth; Daiken, Leslie; et al. (Facets Video, 2007)
The term "Free Cinema" was coined by critic and filmmaker Lindsay Anderson in early 1956 when he, Karel Reisz, Tony Richardson and Lorenza Mazzetti showed a programme of their short films at the National Film Theatre. Although the name was intended only for that screening, it proved so successful that five more programmes were shown under the same banner between 1956 and 1959. [www.play.com]
Keywords: DVD-Video